(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was conducted to record the occurrence of Myxomycetes belonging to the genus Comatricha. The present study was conducted from south-east Maharastra, including Sangali, Satara, Solapur, and Kolhapur districts. Comatricha dictyospora , Comatricha longa, Comatricha longipila, Comatricha pulchela, Comatricha typhoides were the five species of myxomycets recorded in the present study. All the species are being reported for the first time in this region. Of these five species Comatricha dictyospora species of myxomycets was newly recorded in India.